2x-5x+(8x+6x)=x

Simple and best practice solution for 2x-5x+(8x+6x)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5x+(8x+6x)=x equation:


Simplifying
2x + -5x + (8x + 6x) = x

Combine like terms: 8x + 6x = 14x
2x + -5x + (14x) = x
2x + -5x + (14x) = x

Combine like terms: 2x + -5x = -3x
-3x + (14x) = x

Combine like terms: -3x + (14x) = 11x
11x = x

Solving
11x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
11x + -1x = x + -1x

Combine like terms: 11x + -1x = 10x
10x = x + -1x

Combine like terms: x + -1x = 0
10x = 0

Divide each side by '10'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| a=p+1fora | | -208=4x+7(-6x-8) | | -208=4c+7(-6x-8) | | -10-5v+1+8v=7+7v | | 12xy=24 | | a^3x-b^3=0 | | (1+i)z-2i=4z+1 | | 5(a-4)-(8a)=55 | | -2+4y=19 | | -15-10x=4-3(-2-5x) | | 11-3y=1 | | 3x^2-5x+4+x^2= | | -5+4y=19 | | 1+4x-x=x-5 | | P=4w-8 | | 3/4k-10=1 | | -18=n-4n | | 3.2=-3.8-7 | | -18=2-4n | | 4(2.4x-1.6)-8.6x=-8.3 | | 2x(2y+3)-(2y+3)=7 | | 0=-16x^2-16x+5 | | -9*-2-3y=6 | | 9-3f=60 | | 5h+2(h-11)=-5 | | 7x=8x+-4 | | y=-16x^2-16x+5 | | 3x+12x-7=5x+3 | | X+19x=180 | | -16t^2+40t+40=0 | | (fg)(x)=-16x^2-16x+5 | | .10n+.25(n+5)=5.10 |

Equations solver categories